Complete chorioamniotic membrane separation with constrictive amniotic band sequence and partial extra-amniotic pregnancy: serial ultrasound documentation and successful fetoscopic intervention - Schlehe, Bettina; Elsässer, Michael; Bosselmann, Stephan; Sohn, Christof (Journal of perinatology, 2014)
Chorioamniotic membrane separation (CMS) comprises cases of spontaneous and iatrogenic detachment between the amniotic and chorionic membranes, with various fetal outcomes due to possible complications, particularly the formation of constrictive amniotic bands and preterm rupture of membranes. In the absence of mandatory management standards conservative monitoring is the most reported approach. In the case we present here, close sonographic surveillance afforded us the opportunity to observe the process from CMS to amnion rupture with the formation of constrictive amniotic bands and threatened cord impairment via constrictive margins of the amniotic sac. Despite the complicated background of reduced membranous layers in ruptured CMS, we performed a successful fetoscopic intervention with band release at 24 weeks’ gestation and the pregnancy was prolonged to 34 weeks under close monitoring.
Gesehen am 05.11.2020